Reproductive Oppression Enters the Twenty-First Century: Pressure to Use Long-Acting Reversible Contraception (LARC) in the Context of “LARC First” - Mieke C. W. Eeckhaut; Yuko Hara (Socius, 2023)
The common emphasis on the superior pregnancy protection of long-acting reversible contraception (LARC) may result in medical providers’ pressuring women, especially those belonging to groups experiencing reproductive disciplining, to use LARC. The authors consider reports of having felt pressured to get or keep LARC in the 2021 Delaware and Maryland Survey of Women (1,058 current users and 1,788 ever users of LARC) and examine variation in these outcomes by women’s sociodemographic characteristics. The results reveal a high prevalence of both pressure to get (26 percent of current users) and keep (11 percent of ever users) LARC overall and among young (<25 years) mothers in particular. In addition, pressure to keep LARC is more common among economically disadvantaged, unmarried, and Hispanic women. These findings reveal that in the context of “LARC first” and enduring stratified reproduction, LARC pressure is common, particularly among groups that have long been targets of reproductive disciplining.